Fondling Breasts and Playing Guitar. Textual and Contextual Expressions of a Sociomusical Conflict in Accra - Tobias Robert Klein (Zeitschrift der Gesellschaft für Musiktheorie)
The Ga religious authorities in Accra traditionally impose a ban on drumming and noise-making in advance of the annual Homowo festival. Its violation by charismatic churches sparked off a fierce debate on the freedom of worship, in which traditional religion quarrels with Africanised congregations, for whom electric guitars, dances and tongue-speaking form part and parcel of their services. A satirical La Kpa song translates this tension into a socio-(e)motional system of movement, mimics and gestures. Its association of guitar-plucking with the fondling of female breasts establishes an acerbic acoustical allusion to charismatic worshipping practices. The wider aim of this article is to emphasise the need for a combination of cultural, historical and scientific competences in bridging the gap between a contextually inclined ethnomusicology and text-based music theory. The song’s musical and textual variations will thus – with due attention to its dense textual and performative strategies – simultaneously be described as social, cognitive, bodily and structural entities.